Analisis Kesalahan Penggunaan Bahasa Indonesia pada Penulisan Papan Nama, Spanduk, Pamflet di Kecamatan Medan Denai - Arif Rizky Harahap; Nirmawan Nirmawan (Education & Learning, 2023)
This study aims to describe what forms are found in the analysis of Indonesian language usage errors in the writing of signboards, banners, and pamphlets in Medan Denai District. The research method used is descriptive research method whose data is already listed on the writing of signboards, banners, and pamphlets. The instrument used by the researcher in collecting data is from the form of documentation which is done by photographing or taking data in the form of pictures/photos on the subject and object under study, and assisted by a research tool in the form of a cellphone (HP) or smartphone. The data collection techniques used in this research are (1) observation techniques, (2) documentation techniques, and (3) recording techniques. The data analysis technique in this research is descriptive with the steps of (1) searching for data, (2) documenting data, (3) selecting and choosing data, (4) analyzing data and giving marks, (5) identifying data, (6) completing the data that has been obtained, (7) understanding the overall data that has been selected, and (8) concluding the research results. Based on the results of the study, it can be concluded that language errors in the use of spelling, punctuation, word choice, and standardized language vocabulary and non-standardized language vocabulary are still commonly found on signboards, banners, and pamphlets in Medan City, especially in Medan Denai District. The image data obtained by the researcher in accordance with his research amounted to 30 image data that had been taken in the North Sumatra region, specifically in Medan Denai District. The data were categorized by looking at the objects that have been determined by the researcher in his research which are Indonesian language usage errors in writing signboards, banners, and pamphlets. Therefore, the results of the language errors that have been analyzed are as follows: errors in the use of spelling on signboards, banners, and pamphlets amounted to 5 data; errors in the use of punctuation on signboards, banners, and pamphlets amounted to 5 data; errors in the use of word choice (diction) on signboards, banners, and pamphlets amounted to 1 data; and errors in the use of non-standard language vocabulary on signboards, banners, and pamphlets amounted to 9 data; and errors in the use of foreign language terms or elements on signboards, banners, and pamphlets amounted to 5 data